2011
DOI: 10.1155/2011/381928
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Surface Epithelium in Patients with Severe Ovarian Infertility: A Potential Source of Cells Expressing Markers of Pluripotent/Multipotent Stem Cells

Abstract: The aim of this study was to confirm the presence of stem cells in the ovarian surface epithelium of patients with premature ovarian failure and no mature follicles and oocytes. In these patients, small round cells of unknown origin expressing SOX-2 marker of pluripotency were observed among the epithelial cells just after the ovarian surface epithelium scraping. These cells were an integral part of the ovarian surface epithelium. When the scraped cells were cultured in a medium with added follicular fluid to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 49 publications
6
57
0
Order By: Relevance
“…2D) and mesonephric ( Fig. 2A) somatic cells were immunonegative at all stages examined, as was the ovarian surface epithelium, despite recent reports of the isolation of LIN28-positive germ cell-like cells from the adult ovarian surface epithelium [30], and the expression of LIN28 by a subpopulation of epithelial ovarian cancer cells [31]. Negative controls also displayed no staining (Fig.…”
Section: Stem Cells and Developmentmentioning
confidence: 82%
“…2D) and mesonephric ( Fig. 2A) somatic cells were immunonegative at all stages examined, as was the ovarian surface epithelium, despite recent reports of the isolation of LIN28-positive germ cell-like cells from the adult ovarian surface epithelium [30], and the expression of LIN28 by a subpopulation of epithelial ovarian cancer cells [31]. Negative controls also displayed no staining (Fig.…”
Section: Stem Cells and Developmentmentioning
confidence: 82%
“…Immunostaining of ovaries from 7 days, 2 month and 20 months old mice were performed according to previously published procedures [8]. The primary antibodies used in this study were as follows: anti-MVH (1:100, ab27591), anti-OCT4 (1:100, ab18976), anti-YAP1 (1:100, ab56701), anti-LATS2 (1:100, ab54073), and anti-MST1 (1:100, ab51134).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the rates of oocyte atresia and clearance, these germ cells are needed to continuously replenish the follicle pool. Currently, several research groups have demonstrated the isolation of germline stem cells from the ovarian surface epithelium (OSE) of adult and even menopausal mouse and human ovaries [8,9,10] and have also successfully isolated and characterized long-term cultured ovarian germline stem cells (OGSCs) from neonatal and adult mouse ovaries [11,12,13,14,15,16,17]. However, the OSE layer has also been confirmed to be a normal, naturally present source of oocytes by producing stem cells in the embryonic or fetal period of life, and it is commonly referred to as the ‘‘germinal'' epithelium [18].…”
Section: Introductionmentioning
confidence: 99%
“…Putative stem cells were found in the adult ovarian surface epithelium of different mammals, including humans [61,[78][79][80], in mouse ovarian stroma [21] and in the theca layer [29], which surrounds the developing follicle.…”
Section: Expression Of Stem Cell Markers In Granulosa Cells From Follmentioning
confidence: 99%